Google : how Google works (2017) - Schmidt, Eric, 1955 April 27-; Rosenberg, Jonathan, 1961-; Eagle, Alan (Grand Central Publishing, 2017)
Two senior executives at Google discuss their sometimes opposing views on hiring, managing, and motivating their employees and how to best guide business strategies when consumers have all the power.